“İNSAN KAYNAĞI GELİŞTİRME UZMANI YETERLİKLERİ ÖLÇEĞİ”NIN GELİŞTİRİLMESİ - Özer, Bekir (Anadolu Üniversitesi Eğitim Fakültesi Eğitim Bilimleri Bölümü, 1990)
in this study, the competencies reauired by the human resource development (HRD) specialists were determined, and an assessment instrument ofthose competencies was developed. For this purpose, the literatüre on the subject was studied, interviews were held with some academic personnel at the university and some professionals in the organızations, and the assessment instrument was applied to 78 HRD specialists working in different organizations. At the end of the investigation, 36 competencies were determined and they were used as the items of the assessment instrument. in the testing of the internal consistency of the assessment instrument. Cronbach's alpha was found as .95. The suggestions made by the academic personnel of the university for determining the competencies were accepted suitablefor the content validity. in thefactor analyses which were made for testing the construct validity, factor loadings were found rather high and the items in the instrument were gathered infour groups. The findings indicated that the instrument proved to have acceptable reliability and validity for assessing -especially for şelf assessing- the comptencies of the HRD specialists in Turkey.
The file in this item is the publisher version (published version) of the article.
Keywords: İnsan Kaynağı Geliştirme; GÜVENİRLİLİK